Intrinsic and extrinsic effects near orthorhombic-tetragonal phase transition in barium titanate ceramics doped with small amounts of zirconium. Issue 6 (15th April 2017) - Amarande, L.; Miclea, C.; Cioangher, M.; Pasuk, I.; Iuga, A.; Pintilie, I.
Abstract: Pure BT and BT doped with 1 and 2 mol% Zr, with orthorhombic-tetragonal (O-T) phase transitions near room temperature were prepared, with different grain sizes, by conventional ceramic method, at various sintering temperatures. Intrinsic and extrinsic effects of Zr addition on structural, dielectric, piezoelectric and ferroelectric properties of BT ceramics, near O-T phase transition were studied. In coarse grained ceramics, the intrinsic effects manifested in low field measurements (dielectric and piezoelectric constants), were reduced by Zr addition, while the extrinsic effects which control the high field response (remanent polarization and coercive field) were significantly enhanced. Instead, in fine grains ceramics, of either pure or doped BT, the extrinsic effects related to increased domain wall and grain boundaries density were dominant in both low and high field measurements, overlapping Zr effects. The results were explained in terms of crystal anisotropy correlated with grain size effects.